Differential Host Pro-Inflammatory Response to Mycobacterial Cell Wall Lipids Regulated by the Mce1 Operon - Petrilli, Jéssica D.; Müller, Igor; Araújo, Luana E.; Cardoso, Thiago M.; Carvalho, Lucas P.; Barros, Bruna C.; Teixeira, Maurício; Arruda, Sérgio; Riley, Lee W.; Queiroz, Adriano (Frontiers in Immunology, 2020)
The cell wall of wild-type (WT) Mycobacterium tuberculosis (Mtb), an etiologic agent of tuberculosis (TB) and a Mtb strain disrupted in a 13-gene operon mce1 (Δmce1) varies by more than 400 lipid species. Here, we examined Mtb lipid-induced response in murine macrophage, as well as in human T-cell subpopulations in order to gain an insight into how changes in cell wall lipid composition may modulate host immune response. Relative to WT Mtb cell wall lipids, the non-polar lipid extracts from Δmce1 enhanced the mRNA expression of lipid-sense nuclear receptors TR4 and PPAR-γ and dampened the macrophage expression of genes encoding TNF-α, IL-6 and IL-1β. Relative to untreated control, WT lipid-pre-stimulated macrophages from healthy individuals induced a higher level of CD4-CD8- double negative T-cells (DN T-cells) producing TNF-α. Conversely, compared to WT, stimulation with Δmce1 lipids induced higher mean fluorescence intensity (MFI) in IL-10-producing DN T cells. Mononuclear cells from TB patients stimulated with WT Mtb lipids induced an increased production of TNF-α by CD8+ lymphocytes. Taken together, these observations suggest that changes in mce1 operon expression during a course of infection may serve as a strategy by Mtb to evade the host proinflammatory responses.